Tumpi ethnicity (today Tumbes) - Espinoza Soriano, Waldemar (2017)
Tallán Manor speaks located at the northern end of the coastal space CHIMAR empire. Pervivía thanks to permanent river flowing and your name down Loja. His hot weather allowed reproduction even caimans (alligators). Its inhabitants engaged in agriculture and very active sea fishing, also devoted much of his life to making various styles of boats, the most common of them the wooden rafts Ochroma that, rudder, an chor and sail favored navigation over long distances, as is to Chincha and beaches of western Panama Strombus conch shells and exchanged So Galeatus with bronze, gold, fabrics and other Andean objects.